Memori Kolektif Masyarakat Mengenai Bencana Gempa Di Nagari Tandikek Tahun 2009 - Zulhana Ludin (CV. Ulil Albab Corp, 2026)
This study aims to examine the collective memory of the Tandikek Nagari community regarding the earthquake disaster that occurred in 2009. This study uses a qualitative method that is descriptive-narrative. The steps in historical research include: 1) The researcher's heuristics are two sources, namely, primary sources and secondary sources. The primary source of the researcher is the results of interviews with the Tandikek Nagari community regarding collective memory regarding the earthquake disaster in 2009, and documentation of the Lubuak Laweh earthquake monument. While the secondary source of the study uses journals and articles and several YouTube channels that discuss the earthquake event: 2) Source criticism compares and verifies the data obtained from interviews with the community: 3) Interpretation is a very important step in research interpreting the data obtained during research in Tandikek Nagari: 4) Historiography of research writing in the form of a thesis. The results of the study found that the Tandikek Nagari community has made various efforts to maintain collective memory regarding the earthquake disaster such as building monuments, commemorating every year and integrating lessons about the earthquake into the school curriculum, research contributes to the understanding of the community's collective memory regarding the earthquake disaster.